TEKNIK DAN PENDEKATAN PENANAMAN NILAI DALAM PROSES PEMBELAJARAN DI SEKOLAH - Ali Muhtadi (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Values are what people believe to be right and are standardv tojudge something to be good, right, valuable and precious. Valuesdrive people 's live, give meanings to live and legalize people'sbehaviors. Therefore, individual's values can have effects onsociety and national characteristics.Education seems to fail to educate universal values such ashonesty, patience, modesty and trustworthy. This is becauseeducational process that occurred lately is so merely mechanisticlearning that negelected the essence of education as wizys tointernalize universal values in life.There are some learning techniques for teachers to use ineducating value to their students, such as indoctrination technique,moral reasoning technique, consequence forecasting technique,clnrification technique and internalization technique. Theapproaches that teacher can use to educate value through learningprocess al school are experience approach, making it accustomed,emotional, rational, functional and role model approach.